1997
DOI: 10.1023/a:1026419023481
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study evaluated post-treatment performance and quality of life (QOL) outcome in head and neck cancer (HNC) patients treated with organ preservation, intensive chemoradiotherapy (FHX). Participants were 47 Stage II-IV HNC patients with no evidence of disease at least one year post-completion of organ preservation, concomitant FHX treatment. Patients were assessed via a semi-structured in-person interview, standardized measures of QOL (FACT-H&N, CES-D), performance (PSS-HN) and patients' perception of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Depression and other psychosocial morbidities such as anxiety occurred frequently in head and neck cancer patients before and after treatment [ 20 , 21 ]. These reactions are common because cancer and its treatment have always been associated with the idea of death and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and other psychosocial morbidities such as anxiety occurred frequently in head and neck cancer patients before and after treatment [ 20 , 21 ]. These reactions are common because cancer and its treatment have always been associated with the idea of death and suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Total HADS scores (HADS-T) ≥ 15 indicate clinically significant distress. Performance Status Scales (PSS) Normalcy of Diet [ 20 ] measures diet texture restrictions and is clinician-rated. The scale has ten ranked categories ranging from 0 (nil by mouth) to 100 (full diet without restrictions).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 33 included studies, only 12 looked at samples with heterogeneous primary cancers [ 6 , 8 , 20 , 26 , 28 , 29 , 31 - 34 , 37 , 38 ]. Of the 21 studies that looked at patients with only one primary cancer, seven looked at patients with lung cancer [ 12 - 14 , 23 , 25 , 30 , 36 ], four studies observed patients with only head and neck cancers [ 9 , 16 , 24 , 27 ], two looked at only prostate patients [ 7 , 11 ], another two focused on breast patients [ 18 , 21 ], those with only gynecologic cancers were examined in two studies [ 17 , 35 ], one study focused on gastric carcinoma patients[ 19 ], one study analyzed patients with hepatocellular carcinoma [ 15 ], another examined renal cell carcinoma patients [ 22 ] and a further study enrolled patients with pancreatic cancer [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two groups were established-group one contained countries which had per capita health expenditures of less than $2,000 US while studies which came from countries with greater than $2,000 US in per capita expenditures were sorted into a second group. Studies from China, India, the Philippines and South Korea were sorted into group one [ 6 , 13 , 15 , 24 , 25 , 35 , 37 ] while articles from the United States, Canada, Sweden, Japan and Australia were sorted into the second group [ 7 - 12 , 14 , 16 , 17 , 19 - 23 , 26 - 34 , 36 , 38 ]. It was found that patients from countries with low per capita health expenditures had significantly lower levels of physical well-being (weighted mean: 16.87 versus 19.93; P = 0.0110), social/family well-being (mean: 18.51 versus 22.06; P = 0.0164) and relationship with doctors (mean: 6.60 versus 7.27; P = 0.0111) ( Table 2 ); total FACT-G score (including or excluding the relationship with doctor subscale) was not statistically significant (P = 0.5964, P = 0.1652, respectively).…”
Section: Resultsmentioning
confidence: 99%